Therapy online a practical guide - Anthony, Kate.; Nagel, DeeAnna Merz.; Sage eBooks (London : SAGE, 2010)
This title brings the process of online therapy to life with its highly practical approach and use of detailed case material covering the use of email, chat and mobile SMS texting.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Internet in psychotherapy; Internet users -- Psychology; Cyberspace -- Psychological aspects; Electronic books